The potential capability of bacteria and yeast strains isolated from Rungkut Industrial Sewage in Indonesia as a bioaccumulators and biosorbents of copper - WAHYU IRAWATI; ADOLF J.N. PARHUSIP; SALOMO CHRISTIAN; TRIWIBOWO YUWONO (Biodiversitas Journal of Biological Diversity, 2017)
Irawati W, Parhusip Ajn, Christian S, Yuwono T. 2017. The potential capability of bacteria and yeast strains isolated from Rungkut Industrial Sewage in Indonesia as a bioaccumulators and biosorbents of copper. Biodiversitas 18: 971-977. Heavy metal pollution is a serious problem as a result of industrialization due to the high production of wastewaters containing high concentrations of heavy metals. Wastewater contains microbial populations adapted to the toxic concentrations of heavy metals and becomes resistant by accumulating copper inside the cells. The aims of the study were to isolate yeast and bacteria from Rungkut Industrial sewage in Indonesia, and to examine the capability of these isolates to accumulate and biosorb copper. The copper resistance was determined by measuring minimum inhibitory concentration (MIC). The capability of isolates to accumulate and biosorb copper were determined by atomic absorption spectrophotometer. Biosorption is described as how much copper is removed from a growth medium with reference to the initial concentration. Of this study, nine bacterial strains and eight yeast strains were obtained with the MICs of 6-7 mM, and 16-20 mM CuSO4, respectively. Afterward, we have successfully selected three bacteria and one yeast strains showing the highest copper resistance. The three bacterial strains, designated as C1, C2, and C4 were able to accumulate copper up to 29.93, 508.01, 371.42 mg/cell dry weight, respectively. While the yeast strain, ES9.3 was able to accumulate 0.52 mg/cell dry weight and reduce up to 82.32% copper concentration in the medium. The findings of this study indicated that yeast and bacterial strains were promising microorganisms for removal of copper.